2016
DOI: 10.1186/s13071-016-1314-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parallel qPCR provides increased sensitivity and diagnostic breadth for gastrointestinal parasites of humans: field-based inferences on the impact of mass deworming

Abstract: BackgroundAlthough chronic morbidity in humans from soil transmitted helminth (STH) infections can be reduced by anthelmintic treatment, inconsistent diagnostic tools make it difficult to reliably measure the impact of deworming programs and often miss light helminth infections.MethodsCryopreserved stool samples from 796 people (aged 2–81 years) in four villages in Bungoma County, western Kenya, were assessed using multi-parallel qPCR for 8 parasites and compared to point-of-contact assessments of the same sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(204 citation statements)
references
References 60 publications
11
189
3
1
Order By: Relevance
“…Use of the Quik-Chek RDT revealed that, whilst no cryptosporidiosis was encountered, a considerable number of children at Runga and Bugoigo were patently infected with clinically relevant Giardia. This was later confirmed by real-time PCR which, by having greater diagnostic sensitivity 29,[40][41][42] , found a larger proportion of children with some evidence of infection.…”
Section: Discussionmentioning
confidence: 79%
“…Use of the Quik-Chek RDT revealed that, whilst no cryptosporidiosis was encountered, a considerable number of children at Runga and Bugoigo were patently infected with clinically relevant Giardia. This was later confirmed by real-time PCR which, by having greater diagnostic sensitivity 29,[40][41][42] , found a larger proportion of children with some evidence of infection.…”
Section: Discussionmentioning
confidence: 79%
“…Others include schistosome-snail investigations around Lake Victoria. More broadly, the application of DNA-based assays in medical malacology [72] also coincided with the rise in DNA diagnostic assays [19], such as real-time PCR approaches with TaqMan® probes, for medical diagnostics [73, 74]. It is precisely that these medical diagnostic assays have become accepted, standardised and largely routine, that they can be used to spur on interests in environmental surveillance of schistosomes by inspection of water filtrates, environmental samples as well as in field-caught or sentinel snails [65, 66], see Table 1.…”
Section: On Environmental Sampling: Practicalities and Pitfallsmentioning
confidence: 99%
“…Early on in the use of molecular diagnostics for fecal pathogens, there were significant sensitivity problems when DNA extraction techniques that were not specifically designed to remove these inhibitors48 were used. PCR inhibitors are largely removed without problem using 1) more recent in-house developed protocols,27,49 2) tissue kits with additional inhibitor removal steps,24,50 and 3) stool and soil-engineered kits for DNA extraction 19,21,43,5053…”
Section: Technical Considerations In Using Qpcr As An Sth Diagnosticmentioning
confidence: 99%
“…Several large studies have shown a clear relationship between stool DNA concentration as determined by qPCR and egg counts 19,21,43. Interestingly, there is also a good correlation between DNA quantification in the stool (presumably reflecting egg DNA) and the number of expelled adult worms after albendazole treatment 21. The evaluation of the existing data on A. lumbricoides across multiple studies (Table 1) has been aided enormously by the fact that all of the studies have targeted the internal transcribed spacer 1 region (see Table 2).…”
Section: Qpcr In the Detection Of Each Of The Major Sthmentioning
confidence: 99%